Implementasi Media Interaktif Articulate Storyline Pada Pembelajaran Instalasi Tenaga Listrik - Huda, Syamsal; Hendri, Hendri (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2025)
This study aims to analyze the effect of interactive learning media using the Articulate Storyline application on student learning outcomes in the subject of electrical power installation at SMKN 1 Pariaman. The background of this study is the low utilization of interactive learning media, although the use of gadgets among students has increased, it has not been directed to support learning. This study uses an experimental method with a pretest and posttest design with the equivalent control group. The subjects of the study were students of class XI TITL, with samples consisting of an experimental class (32 students) using interactive media and a control class (30 students) using conventional methods. Data collection was carried out through pretests and posttests that had been validated by expert lecturers and subject teachers. The results showed a significant increase in student learning outcomes in the experimental class, with an average post-test score higher than the control class. The t-test produced a significant value indicating a significant difference between the two groups. The N-Gain Score analysis showed quite high effectiveness in the experimental class compared to the control class. In addition, the Cohen's Effect Size calculation produced a value that was included in the